Dual roles of BK Polyomavirus in promoting urothelial carcinoma progression via regulating CLDN1 - Cuidi Xu; Siyue Chen; Juntao Chen; Jina Wang; Xinhao Niu; Ruiming Rong; Tongyu Zhu; Yigang Zeng (BMC, 2024)
Abstract Uncontrolled productive infection of BK polyomaviruses (BKV) in immunocompromised patients was reported to result in serious diseases, especially renourinary malignancies. However, the mechanism of BKV as a role of human carcinogen is still unknown. In this study, we showed that there is a significant association between BKV infection and metastasis of urothelial carcinoma (UCA). BKV-infected tumor tissues exhibit invasive histologic phenomena with vascular invasion and myometrial invasion. Then we identified that BKV promotes UCA invasion in a mode of dual regulation of tumor cells (TCs) invasion and endothelial cells (ECs) adhesion by encoding miRNAs. In cancer cells, BKV-B1-miR-5p promotes cell motility and invasiveness by directly targeting CLDN1. Moreover, exosomal-BKV-B1-miR-3p derived from BK-infected BC cells would be transferred to ECs and increase its adhesion to tumor cells by switching on the CLDN1 enhancer, which subsequently destroyed endothelial monolayers and increased permeability. In a human urothelial cancer metastasis mouse model, BK-inoculated cells exhibited higher incidence of vascular leakage and liver colonization. However, the vascular leakage and liver metastasis could be reduced when knocking down miRNAs in BK-inoculated cells. Our research delineates the bifunctional impact of BKV-encoded microRNAs on the expression of CLDN1 within both TCs and ECs, which orchestrates the establishment of a pre-metastatic niche in UCA.